Modelo morfodinâmico com transporte litorâneo longitudinal e transversal para aplicações de engenharia - Silva, Rodrigo Amado Garcia (2019)
Numerical Models are tools frequently used to study nearshore processes. Several strategies are employed by the various modelling systems to represent the longshore and cross-shore sediment transport in the surf zone. The calibration of these models is a challenge, especially for the case of beach profile evolution models. This work presents a 2DH coastal morphodynamic model for use in Engineering problems. This model consists of the coupling between a model of longshore transport model, already well established and based on the formula of Van Rijn (2007), and cross-shore transport model, which is based on the Kriebel & Dean (1984) formula and is the main subject here studied. The Kriebel & Dean (1984) formula provides the solid discharge, for a given sediment, from the knowledge of the water column at each point of the surf zone, of which values are previously calculated with a hydrodynamic model coupled with a wave model. The model was validated with results of physical model and tested for beach morphodynamics simulation of typical Coastal Engineering problems. One also presents a methodology for prescribing adequate boundary conditions in the open boundaries of coastal hydrodynamic models.